Electrical System Design and Installation of New Building, Aisyiyah University, Yogyakarta - Suripto, Slamet; Jamal, Agus; Purwanto, Kunnu; Wicaksono, Wahyu Nugroho; Jusman, Yessi (Journal of Electrical Technology UMY, 2018)
Aisyiyah University New Yogyakarta Building is one of the commercial buildings that moves the field of education in Yogyakarta. The New Building of Aisyiyah University Yogyakarta consists of 10 floors, including the basement floor, main floor and roof floor. Electric loads installed at the New Building of Aisyiyah University Yogyakarta include lighting loads (lights) and power loads (sockets) and the power loads of electric motors (air conditioners, elevators and others), which of course requires a large enough electricity supply. Electricity installed in the New Building of Aisyiyah University in Yogyakarta is 1010.9 kVA. The power supplied is 800 kVA from State Electricity Company and the total power capacity of the transformer is 1000 kVA and a generator set with a capacity of 1000 kVA. Where the backup power supply system is fully supplied by the generator set.